Cancer stem cells: A product of clonal evolution?. Issue 5 (12th October 2016) - van Niekerk, Gustav; Davids, Lester M.; Hattingh, Suzèl M.; Engelbrecht, Anna‐Mart
Abstract : The cancer stem cell (CSC) model has emerged as a prominent paradigm for explaining tumour heterogeneity. CSCs in tumour recurrence and drug resistance have also been implicated in a number of studies. In fact, CSCs are often identified by their expression of drug‐efflux proteins which are also highly expressed in normal stem cells. Similarly, pro‐survival or proliferation signalling often exhibited by stem cells is regularly reported as being upregulated by CSC. Here we review evidence suggesting that many aspects of CSCs are more readily described by clonal evolution. As an example, cancer cells often exhibit copy number gains of genes involved in drug‐efflux proteins and pro‐survival signalling. Consequently, clonal selection for stem cell traits may result in cancer cells developing "stemness" traits which impart a fitness advantage, without strictly following a CSC model. Finally, since symmetric cell division would give rise to more cells than asymmetric division, it is expected that more advanced tumours would depart from a CSC. Collectively, these observations suggest clonal evolution may explain many aspects of the CSC.